Weight Gain, Feed Consumption, and Feed Efficiency of Kampong Chicken at the Grower Phase Supplemented with Propionic Acid - Lisnahan, Charles Venirius; Elu, Clarissa Dorince; Pasi, Maria Selfiana; Tae, Agustina Viktoria (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
The study aimed to determine the effect of adding propionic acid in feed on the growth of Kampung chickens in the grower phase was conducted from July to September 2024 in Kefamenanu City, North Central Timor Regency. A total of 80 Kampung chickens aged 6 weeks with an average body weight of 400 g were used in this study. The method used was a Completely Randomized Design, consisting of 4 treatments and 4 replications, each replication consisting of 5 chickens. The treatments given were T0: control feed (without propionic acid), T1: control feed + 0.20% propionic acid, T2: control feed + 0.40% propionic acid, T3: control feed + 0.60% propionic acid. The research variables observed were weight gain, feed consumption and feed efficiency. Data analysis used analysis of variance and Duncan's multiple range test. The results showed that the average weight gain of T0, T1, T2, and T3 were 103.41±1.94, 106.07±0.58, 108.72±1.14, 109.61±1.84 g/head/week, respectively. Feed consumption was 496.83±2.82, 500.89±2.07, 502.58±1.41, 504.74±9.36 g/head/week, respectively. Feed efficiency was 20.81±0.29, 21.17±0.07, 21.63±0.20, 21.71±0.05%/head, respectively. Analysis of variance showed that the treatment had a significant effect (P<0.05) on weight gain and feed efficiency, while feed consumption was not significant. It was concluded that the use of propionic acid at a level of 0.60% in feed provided maximum results on the performance of Kampung chickens in the grower phase.